A Jurisprudential Review of Business Competition Practices on the Shopee Platform: Unfair Practices and Their Impact on Small Businesses - Munawaroh, Diyan (Institut Agama Islam Negeri Ponorogo, 2024)
The rapid development of technology has transformed conventional business practices, with digital platforms such as Shopee providing innovative features, such as live streaming and flash sales. However, these features have the potential to enable unfair business competition. This study examines the impact of live streaming on Shopee Live and Toko Saya flash sales on a Shopee platform from the perspective of business competition. Using a qualitative approach, this study focuses on the policies and practices surrounding these features. The findings reveal that while certain promotional practices are legitimate, the ongoing practice of providing conditional discounts and low prices may violate business competition laws and principles of business competition jurisprudence in Islam. Sellers and buyers have indicated that these practices are not based on the principles of honesty and balance and can be detrimental to smaller businesses with limited capital. This study highlights the need for businesses to prioritize moral ethics and adhere to religious and state rules to create a fair and competitive market that protects consumer rights. As digital platforms continue to grow, it is crucial to address the potential for unhealthy business competition and to ensure that all parties, including conventional business actors, can participate fairly in the market.